Survival in Sensitized Lung Transplant Recipients With Perioperative Desensitization. Issue 2 (February 2015) - Tinckam, K. J.; Keshavjee, S.; Chaparro, C.; Barth, D.; Azad, S.; Binnie, M.; Chow, C. W.; de Perrot, M.; Pierre, A. F.; Waddell, T. K.; Yasufuku, K.; Cypel, M.; et al.
<x xml:space="preserve">Abstract</x> Donor‐specific HLA antibodies (DSA) have an adverse effect on short‐term and long‐term lung transplant outcomes. We implemented a perioperative strategy to treat DSA‐positive recipients, leading to equivalent rejection and graft survival outcomes. Pretransplant DSA were identified to HLA‐A, B, C, DR and DQ antigens. DSA‐positive patients were transplanted if panel reactive antibody (PRA) ≥30% or medically urgent and desensitized with perioperative plasma exchange, intravenous immune globulin, antithymocyte globulin (ATG), and mycophenolic acid (MPA). PRA‐positive/DSA‐negative recipients received MPA. Unsensitized patients received routine cyclosporine, azathioprine and prednisone without ATG. From 2008–2011, 340 lung‐only first transplants were performed: 53 DSA‐positive, 93 PRA‐positive/DSA‐negative and 194 unsensitized. Thirty‐day survival was 96 %/99%/96% in the three groups, respectively. One‐year graft survival was 89%/88%/86% (p = 0.47). DSA‐positive and PRA‐positive/DSA‐negative patients were less likely to experience any ≥ grade 2 acute rejection (9% and 9% vs. 18% unsensitized p = 0.04). Maximum predicted forced expiratory volume (1 s) (81%/74%/76%, p = NS) and predicted forced vital capacity (81%/77%/78%, respectively, p = NS) were equivalent between groups. With the application of this perioperative treatment protocol, lung transplantation can be safely performed in DSA/PRA‐positive patients, with similar outcomes to unsensitized recipients.